2012
DOI: 10.1123/ijspp.7.4.375
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Freely Chosen Cadence and Optimal Cadence in Cycling

Abstract: Purpose:The main aim of this study was to compare the freely chosen cadence (FCC) and the cadence at which the blood lactate concentration at constant power output is minimized (optimal cadence [Copt]). The second aim was to examine the effect of a concomitant change of road incline and body position on FCC, the maximal external power output (Pmax), and the corresponding Copt.Methods:FCC, Copt, and Pmax were analyzed under 2 conditions: cycling on level ground in a dropped position (LGDP) and cycling uphill in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Therefore, one great advantage of JASA method is that the subjects do not have to interrupt the task intermittently to perform isometric contractions, such as the MVC test 34 . Previous reports have shown that reductions in frequency, action potential amplitude, and conduction velocity that occur during static and dynamic muscle contraction are associated with an accumulation of metabolic by-products and changes in the intracellular pH, a feature that varies according to the quality and duration of the exercise 35,36 . We also used the JASA method to consider both RMS and MF over the session.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one great advantage of JASA method is that the subjects do not have to interrupt the task intermittently to perform isometric contractions, such as the MVC test 34 . Previous reports have shown that reductions in frequency, action potential amplitude, and conduction velocity that occur during static and dynamic muscle contraction are associated with an accumulation of metabolic by-products and changes in the intracellular pH, a feature that varies according to the quality and duration of the exercise 35,36 . We also used the JASA method to consider both RMS and MF over the session.…”
Section: Discussionmentioning
confidence: 99%
“…This workload corresponded to the easy/moderate intensity domain. The subjects were free to use their preferred cadence to minimize peripheral fatigue ( 21 ). After the warm-up, the subjects rested for 10 min by sitting on a chair.…”
Section: Methodsmentioning
confidence: 99%
“…Particular emphasis was placed on stride frequency and length on the TMILL, rpm (revolutions per min) on the three different bikes and ELLIP, and the number of strokes per min on the ROW. For this purpose, the current scientific evidence in this regard was considered (28)(29)(30)(31)(32)(33)(34). Study participants also received information regarding the use of the RPE based on the current guidelines (35).…”
Section: Experimental Designmentioning
confidence: 99%